Compensatory and Multiplicative Advantages: Social Origin, School Performance, and Stratified Higher Education Enrolment in Finland - Laura Heiskala; Jani Erola; Elina Kilpi-Jakonen (Oxford University Press, 2025)
The rules of intake, which determine how educational institutions are accessed, play a significant part in generating intergenerational educational inequalities. Different rules may allow parental advantages to compensate for students’ lack of advantages (such as academic performance) or to multiply and help only those students who are in a position to use such additional advantages. In this article, we study compensation and the multiplication of advantages in the context of the Finnish higher education system. Entrance exams and a dual model (universities and polytechnics) make this system stand out among many other Western countries and hence suitable for this study. Using high-quality Finnish register data, we study the associations between parental education and stratified higher education enrolment across the school performance distribution. Our results show that polytechnics provide access for poorly performing students from higher social origins (compensatory advantage). Polytechnic education also attracts well-performing students from lower social origins, which leads to a situation in which well-performing students with higher social origins have a substantially larger probability of enrolling in university compared to well-performing students with lower social origins (multiplicative advantage).